Influence of deciduous molar hypomineralization on the development of molar-incisor hypomineralizarion - Cristiane Maria Costa-Silva; Janice Simpson de Paula; Glaucia Maria Bovi Ambrosano; Fábio Luiz Mialhe (Universidade Estadual de Campinas, 2015)
Defects similar to Molar-Incisor Hypomineralization (MIH) in second primary molars can be found in the literature, being recently named Deciduous Molar Hypomineralization (DMH). Researchers have stated that the presence of DMH in primary dentition represents a risk for MIH in permanent teeth. The explanation for this association is probably related to the etiological factors. Aim: To investigate prospectively the association between DMH and MIH and the etiologic factors involved in both defects. Methods: One hundred and thirty four children aged 4 to 6 years from Botelhos, MG, Brazil, were evaluated six-monthly until they completed the eruption of the first permanent molars. A structured questionnaire was developed with questions about the child's health up to the first year of life and the mother's health during pregnancy. Results: It could be noted that, although most children with DMH in the primary dentition had higher incidence of MIH in permanent dentition, this difference was not statistically significant. Conclusions: None of the possible etiologic factors had associations with the studied enamel defects, even among children who presented two types of enamel defects in the mixed dentition. However, further studies with larger samples should be conducted in order to confirm or refute the findings of the present study.